2021
DOI: 10.1093/gastro/goab050
|View full text |Cite
|
Sign up to set email alerts
|

One stomach, two subtypes of carcinoma—the differences between distal and proximal gastric cancer

Abstract: Gastric cancer (GC) is one of the most common malignant tumors of the digestive tract, posing a significant risk to human health. Over the past 10 years, the pathological characteristics and the prognosis of GC have been determined based on the locations of the tumors that were then classified into two types—proximal and distal GC. This review focuses on the differences in epidemiology, etiology, cell source, pathological characteristics, gene expression, molecular markers, manifestations, treatment, prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 143 publications
0
8
0
Order By: Relevance
“…To our knowledge, the present study reports the largest genomic and transcriptional survey of human IMs to date. Similar to GCs, IMs can involve different stomach regions, with IMs tending to originate in the antrum due to Hp infection [54].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present study reports the largest genomic and transcriptional survey of human IMs to date. Similar to GCs, IMs can involve different stomach regions, with IMs tending to originate in the antrum due to Hp infection [54].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, while GERD is a risk factor for esophageal cancer development ( 50 ), epidemiological studies have not found an association between EoE and esophageal cancer, despite the presence of chronic inflammation ( 51 ). In contrast, reflux has been shown to influence other esophageal conditions such as achalasia and scleroderma, which are both associated with a higher susceptibility to esophageal cancer progression ( 52 , 53 ). Therefore, further exploration of the cellular landscape of EEC in GERD, with a larger cohort of patients, may provide valuable insights into the distinctions among GERD, EoE, achalasia, and scleroderma esophageal diseases and their varying susceptibilities to esophageal cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal GC is common in developing countries and results from the transformation of precancerous lesions such as chronic superficial gastritis to atrophic gastritis, intestinal metaplasia, and dysplasia into cancer. Diffuse GC is a non-differentiated form in which the tumor cells are disorganized, have less glandular structure, and are not associated with precancerous lesions [ 10 ]. The pathogenicity of H. pylori is increased due to factors that induce apoptosis and cell proliferation.…”
Section: Introductionmentioning
confidence: 99%